THE ROLE OF GREEN INNOVATION IN CATALYZING CIRCULAR ECONOMY PRACTICES TO ENHANCE SUSTAINABILITY PERFORMANCE IN THE ELECTRICAL AND ELECTRONIC INDUSTRY - Ghazali, Putri Nur Azalea; Shaharudin, Mohd Rizaimy; Akbar, Jamaludin; Wararatchai, Preecha (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
As global concerns over environmental damage and resource scarcity, the Electric and Electronic (E&E) industry faces increasing pressure in enhancing its sustainability performance. Even though more focus is given to sustainability, limited research on the relationship between green innovation and circular economy practices in enhancing sustainability performance in this sector is being studied. Thus, this study aims to investigate the role of green innovation in driving sustainability performance and examine how circular economy practices affect and mediate this relationship within the E&E industry. The conceptual framework was developed based on two theories, which are the resource-based view (RBV) and natural-resource-based view (NRBV) theories. Both theories were used to explore the connection between green innovation, circular economy practices, and also sustainability outcomes. Using a narrative review approach, it aims at synthesizing and interpreting the data from the existing literature, specifically in E&E firms. The findings revealed that green innovation significantly contributes to improved environmental, economic, and social performance. Moreover, circular economy practices not only directly enhance sustainability performance but also help in mediating the effect of green innovation. This shows their function as a strategic enabler. This study uses a theory which enhances previous models by integrating RBV and NRBV. These theories explain how firms can build sustainable competitive advantage through innovation and resource circularity. From a practical perspective, this study offers important guidance for industry stakeholders and policymakers who aimed at adopting integrated green and circular strategies to achieve long-term sustainability. Since the study focuses solely on the E&E sector in a specific regional context, future research should examine a wider range of industries and include other moderating variables to broaden and enhance the understanding of this subject matter.